High Performance Thin Layer Chromatography (HPTLC): A Modern Analytical Tool for Chemical Analysis - Jain, Ankita; Parashar, A K; Nema, R K; Narsinghani, T (Current Research in Pharmaceutical Sciences, 2014)
HPTLC is a most versatile technique and is known for uniformity, purity profile, assay values and precision and accuracy of results. It can handle several samples of even divergent nature and composition. HPTLC is a modern analytical separation method with extensive versatility, although already much utilized, is still with great potential for future development in research and development. It is accepted as a time-saving and most economical machine practically with minimum trouble shootings. It speeds up analysis work which is usually not possible with other parallel chromatographic techniques available. The scope of hyphenation of HPTLC with other analytical techniques appears to hold considerable promise for the analysts who previously have had reservation towards the use of planar chromatography. Its hyphenation with mass/infra red/laser spectroscopy, etc. opens a new dimension which makes it the most prestigious among the analytical chemists in the present perspective. In this article, we present a practical view of the concepts of various parameters in the validation fields of quantitative high-performance thin layer chromatography analytical methods in pharmaceutical analysis, as well as several recent methods to serve as an introduction to applications of analytical validation, whether they are for an academic or an industrial researcher.